Dysembryoplastic neuroepithelial tumor. Presentation of an atypical case. - Abreu Casas, Duniel; Alemán Bacallao, Alfredo; Salinas Olivares, Mercedes Rita; Fornaris Cedeño, Yasmany (Revista Argentina de Neurocirugía, 2024)
The case of a patient with a dysembryoplastic neuroepithelial tumor (DNT) with atypical location and clinical behavior is presented in order to describe the diagnostic-therapeutic behavior and the established follow-up.A 44-year-old male patient presented a picture of central facial paresis and left brachial monoparesis of two months' evolution. The contrasted magnetic resonance imaging study defines a right frontal cystic lesion with little perilesional edema, without contrast enhancement. Neuronavigation-guided surgical treatment was performed, achieving total resection of the lesion, with favorable evolution.ODD is a mixed neuroglial tumor associated with epilepsy in children and young adults. They are located more frequently supratentorially in the cerebral cortex with a predilection for the temporal lobe (80%). MRI shows well-defined lobulated cysts located in the cerebral cortex. Extension to the subcortical white matter in cases like this is considered rare. The predominant and most effective treatment in symptomatic cases of DNT is total resection of the tumor.The frontal and subcortical location, the large size of the cyst, and the clinical debut with motor defect in the absence of seizures are unusual forms in the presentation of ODD. Pathological studies are key in the diagnosis and differentiation of other glial tumors with similar behaviour. Total macroscopic resection of the tumor generally allows cure and improvement or disappearance of symptoms.
Keywords: Brain tumor; Dysembryoplastic Neuroepithelial Tumor; Magnetic Resonance Imaging; Seizures